MINI REVIEW: SINTESIS DAN KARAKTERISASI NANOPARTIKEL CaO DARI CANGKANG TELUR MENGGUNAKAN METODE KALSINASI - Zahra, Marinda Afifatu; Hiyahara, Irfan Ashari; Syaima, Husna (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2024)
This review article aims to collect, compare and analyze the latest research on the synthesis and characterization of CaO nanoparticles from eggshells. CaO is a material in the form of white crystalline solids made from thermal decomposition of limestone or shells, which contains CaCO3 which has the potential to become CaO nanoparticles to be applied in various fields. Currently, various methods have been carried out to synthesize these materials, such as precipitation methods, hydrothermal methods, sol-gel methods, and so on. One of them is the calcination method. The calcination method itself is a commonly used thermal processing method involving heating at high temperatures. The advantages of the calcination method are that it is efficient, has a high level of purity, is economical and relatively simple and others. However, the calcination method itself has disadvantages, namely the process time is quite long, must be careful and can have a negative impact on the environment. In this review, we will discuss the synthesis of CaO nanoparticles characterized using X-Ray Diffraction (XRD), Fourier Transform InfraRed (FTIR), Scanning Electron Microscope (SEM), Transmission Electron Microscope (TEM). The literature results show that in XRD the main peak 2θ positions are 111 and 200 and the crystal size is 10-55 nm, in FTIR the functional groups that appear are the Ca-O stretch group and C-O stretch vibrations, in SEM and TEM the shape of the crystal. Keywords: Synthesis, CaO nanoparticles, Calcination